Selective cytotoxic and anti-metastatic activity in DU-145 prostate cancer cells induced by Annona muricata L. bark extract and phytochemical, annonacin - Kimberley Foster; Omolola Oyenihi; Sunelle Rademan; Joseph Erhabor; Motlalepula Matsabisa; James Barker; Moses K. Langat; Amy Kendal-Smith; Helen Asemota; Rupika Delgoda (BMC, 2020)
Abstract Background Annona muricata L. was identified as a popular medicinal plant in treatment regimens among cancer patients in Jamaica by a previously conducted structured questionnaire. Ethnomedically used plant parts, were examined in this study against human prostate cancer cells for the first time and mechanisms of action elucidated for the most potent of them, along with the active phytochemical, annonacin. Methods Nine extracts of varying polarity from the leaves and bark of A. muricata were assessed initially for cytotoxicity using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay on PC-3 prostate cancer cells and the ethyl acetate bark (EAB) extract was identified as the most potent. EAB extract was then standardized for annonacin content using High-performance Liquid Chromatography - Mass Spectrometry (HPLC-MS) and shown to be effective against a second prostate cancer cell line (DU-145) also. The mode of cell death in DU-145 cells were assessed via several apoptotic assays including induction of increased reactive oxygen species (ROS) production, reduction of mitochondrial membrane potential, activation of caspases and annexin V externalization combined with morphological observations using confocal microscopy. In addition, the potential to prevent metastasis was examined via inhibition of cell migration, vascular endothelial growth factor (VEGF) and angiogenesis using the chorioallantoic membrane assay (CAM). Results Annonacin and EAB extract displayed selective and potent cytotoxicity against the DU-145 prostate carcinoma cells with IC50 values of 0.1 ± 0.07 μM and 55.501 ± 0.55 μg/mL respectively, without impacting RWPE-1 normal prostate cells, in stark contrast to chemotherapeutic docetaxel which lacked such selectivity. Docetaxel's impact on the cancerous DU-145 was improved by 50% when used in combination with EAB extract. Insignificant levels of intracellular ROS content, depolarization of mitochondrial membrane, Caspase 3/7 activation, annexin V content, along with stained morphological evaluations, pointed to a non-apoptotic mode of cell death. The extract at 50 μg/mL deterred cell migration in the wound-healing assay, while inhibition of angiogenesis was displayed in the CAM and VEGF inhibition assays for both EAB (100 μg /mL) and annonacin (0.5 μM). Conclusions Taken together, the standardized EAB extract and annonacin appear to induce selective and potent cell death via a necrotic pathway in DU-145 cells, while also preventing cell migration and angiogenesis, which warrant further examinations for mechanistic insights and validity in-vivo.